Implementasi Nilai Zakat sebagai Media Pendidikan Kepedulian Sosial di Sekolah - Tauhid, Imam; Oktaviona, Gita; Listianti, Dinda Nayla (Jurnal Pendidikan Tambusai, 2026)
Social concern education in schools faces challenges amid student individualism in the digital era, where Islamic values like zakat offer untapped potential for character building. This study aims to analyze zakat implementation as a medium for fostering social awareness among students. Employing a qualitative library research approach with descriptive-analytic methods, the population comprises primary Islamic sources and secondary literature on zakat in education, purposively sampling 25 key documents including Qur'anic verses, hadiths, and recent journals (2020-2025). Instruments include Al-Qur'an, fiqh texts, and modern publications, analyzed via systematic review, thematic categorization, and source triangulation. Findings reveal zakat's etymological essence (zakā: purification, growth) embodies 10 educational values—faith reinforcement, gratitude, anti-stinginess, justice, humanity, work ethic, social care—supported by conditions like nisab and haul, yielding societal impacts such as poverty alleviation and collective responsibility. In conclusion, zakat integration into school curricula effectively cultivates empathetic, responsible student character.